Atomic and Electronic Structure of Pilus from Geobacter sulfurreducens through QM/MM Calculations: Evidence for Hole Transfer in Aromatic Residues - Mezzina Freitas, Luis Paulo [UNESP]; Feliciano, Gustavo Troiano [UNESP] (American Chemical Society (ACS), 2021)
Long-range electron transport has been widely and experimentally reported in Geobacter sulfurreducens pilus protein. However, a better understanding of the still undefined molecular arrangement can bring to light the role of key residues in this phenomenon. We propose a theoretical investigation of the electronic structure of aromatic residue groups in the protein through a classical molecular dynamics (MD) simulation, followed by a quantum mechanics/molecular mechanics (QM/MM) electronic study of different frames sampled from MD trajectories, an electrostatic potential and electron density analysis, an analysis of the density of states, and an investigation of hole formation through Dyson orbital calculations. We observe a highest occupied molecular orbital-lowest unoccupied molecular orbital (HOMO-LUMO) energy gap in the ranges of 1.4-2.3 eV and 2.9-3.3 eV and a less intense dipole moment along the aromatic residues in the presence of water in comparison to the system in vacuum. HOMO and LUMO electron densities highlight the occupation of one tyrosine residue in every representation for HOMO and a delocalization along two to three rings for LUMO. The results show how the electronic structure of the aromatic residues is sensitive to the ring arrangement and the surrounding environment. In our study, we observe that slight rearrangements in the fiber geometry can create temporary conditions for hole transfer.